2010
DOI: 10.1039/c0cp00605j
|View full text |Cite
|
Sign up to set email alerts
|

Long-range electron transfer in recombinant peroxidases anisotropically orientated on gold electrodes

Abstract: Long-range electron transfer (ET) in horseradish peroxidase (HRP) was studied with a wild-type recombinant form of HRP, rHRP, and recombinant forms containing histidine and cysteine tags at Gln1, Asn57, Asn189, or Ser309 amino acid residues of the protein. Chemisorption of the enzyme onto the Au electrodes through the tags introduced in different positions of the protein surface provided anisotropic orientations of the rHRPs on the Au surface, which allowed a restricted "rotation" of the rHRP molecules on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 75 publications
3
36
0
Order By: Relevance
“…2. First, it is an essentially low-efficient O 2 reduction at potentials over the thermodynamic potentials for the T1 site of the laccase, which may be ascribed to a slow transfer of the first e À , and, second, a much more efficient O 2 reduction reaction at higher overpotentials, with a current of O 2 reduction levelling at 17 lA cm À2 at 0 V. Such moderate bioelectrocatalytic currents are likely to result from the low surface coverage with bioelectrocatalytically active laccase molecules, consistently with a similar data on another redox enzyme, horseradish peroxidase, involved in the direct ET reaction with graphite [43] and gold [16]. DPV analysis supported this assumption, since only a very poor DPV oxidation signal, at the level of artefact, was observed with laccase-GA-cross-linked graphite electrodes.…”
Section: Bioelectrocatalysis Of O 2 Reduction Catalysed By Laccase Atsupporting
confidence: 72%
See 1 more Smart Citation
“…2. First, it is an essentially low-efficient O 2 reduction at potentials over the thermodynamic potentials for the T1 site of the laccase, which may be ascribed to a slow transfer of the first e À , and, second, a much more efficient O 2 reduction reaction at higher overpotentials, with a current of O 2 reduction levelling at 17 lA cm À2 at 0 V. Such moderate bioelectrocatalytic currents are likely to result from the low surface coverage with bioelectrocatalytically active laccase molecules, consistently with a similar data on another redox enzyme, horseradish peroxidase, involved in the direct ET reaction with graphite [43] and gold [16]. DPV analysis supported this assumption, since only a very poor DPV oxidation signal, at the level of artefact, was observed with laccase-GA-cross-linked graphite electrodes.…”
Section: Bioelectrocatalysis Of O 2 Reduction Catalysed By Laccase Atsupporting
confidence: 72%
“…That can be done through the attachment of the enzyme to the electrode through the specific groups introduced e.g. by genetic engineering [16] or by orientating the enzyme at the electrode surface by means of the electrode-confined promoter molecules having high affinities for specific ET-favouring surface domains of the enzyme [4,17,18]. In the latter case, aromatic molecules grafted onto electrodes and structurally mimicking the enzyme substrates allowed stable and efficient bioelectrocatalysis of O 2 reduction by several fungal laccases [4,17] and another ''blue copper'' enzyme, bilirubin oxidase [18], under vigorous stirring conditions that allowed to overcome oxygen diffusion limitations.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve enzyme orientation on solid and conductive supports, hence favoring DET processes, two main ways have been reported recently: 1) genetic engineering on the protein to provide suitable residues, [170] and 2) modification of the electrode to fit some residues located near the surface electronic relay.…”
Section: Chemelectrochem Reviewsmentioning
confidence: 99%
“…This approach demonstrated that a distribution of orientations is adopted and that the enzymes possibly immobilize as monomers and dimers. A recombinant horseradish peroxidase bearing His-or Cys-tags at different positions with respect to the heme active site was attached to a gold electrode via the tag [155]. AFM measurements were performed in liquid (in 150 µL PBS), i.e., in an environment able to preserve the enzyme native structure (as far as it can be preserved on a solid surface).…”
Section: Microscopymentioning
confidence: 99%